Contemporary work: Its meanings and demands. (April 2017) - Findlay, Patricia; Thompson, Paul
This article addresses recurrent trends in the forces shaping work and its meanings. Using evidence from large-scale surveys and qualitative case studies it maps the changing picture of work and employment, particularly in the UK and Australia. It does so by focusing on insecurity, demanding work, performance management, work–life boundaries and dis/engagement. Whilst identifying a number of negative impacts of change such as growing insecurity and excessive work pressures, the article emphasises that these are trends, not universals, and don't affect all workers or affect them in the same way. We need to be more careful about how trends are translated into overarching theoretical constructs that give a misleading picture. In policy terms, attention should be given to the intersection of labour process and labour market factors, the changing boundaries between and shared aspirations of 'standard' and 'nonstandard' workers, and to a more nuanced understanding of the positive elements of 'bad' jobs and the more negative elements of 'good' ones.